Determinação espectrofotométrica por injeção em fluxo de glifosato em formulações comerciais de herbicidas - Silva, Aline Santana da [UNESP]; Pezza, Leonardo [UNESP]; Pezza, Helena Redigolo [UNESP] (Sociedade Brasileira de Química, 2012)
A flow injection spectrophotometric procedure for the determination of glyphosate in commercial formulations of herbicides is proposed. The determination is based on the reaction of glyphosate and p-dimethylaminocinnamaldehyde, in acid medium, yielding a colored compound (l máx = 495 nm). Under optimal conditions, Beer's law is obeyed in a concentration range 40-640 mg mL-1 with a correlation coefficient of 0.9996. The detection limit was 8.60 mg mL-1 for glyphosate. The method was successfully applied for the determination of glyphosate in commercial formulations of herbicides. Recovery of glyphosate from various commercial samples of herbicides range from 91.0 to 110%.
Flow-injection spectrophotometric determination of glyphosate in commercial formulations of herbicides
Keywords: glyphosate; herbicides; flow injection analysis